Correction: Synthesis and structural characterization of metal complexes with macrocyclic tetracarbene ligands. (1st May 2018) - Fei, Fan; Lu, Taotao; Chen, Xue-Tai; Xue, Zi-Ling
Abstract : Correction for 'Synthesis and structural characterization of metal complexes with macrocyclic tetracarbene ligands' by Fan Fei et al., New J. Chem., 2017, 41, 13442–13453.